Implementasi Khiyar Dalam Jual Beli Sistem Pre Order Online Pada Aplikasi PT Wook Global Technology Cabang Jambi Dalam Meningkatkan Kepuasan Pelanggan - Haqqi Evarizan; Hansen Rusliani; M. Maulana Hamzah (Journal Economic Excellence Ibnu Sina, 2024)
Khiyar is the right to choose to continue or cancel a buying and selling transaction. However, buying and selling in today's society is different from buying and selling in ancient times. In the online buying and selling transaction process, there is a high possibility that undesirable risks will arise from both the seller and the buyer, in this way the right of khiyar or choice becomes very important. The purpose of this research is to find out how khiyar is implemented in the online pre-order system buying and selling on the PT application. Wook Global Technology Jambi Branch in increasing customer satisfaction. The type of research used in this research is a descriptive qualitative method. Data collection techniques consist of observation, interviews and documentation. The data obtained by researchers was analyzed in three steps, namely data reduction, data presentation and data verification. The research results show that the implementation of khiyar in the online pre-order system buying and selling on the PT application. Wook Global Technology Jambi Branch has many non-conforming objects in practice which have implemented khiyar even though in terms of knowledge and literacy they understand or understand khiyar. In the wook application, the khiyar practice applied is khiyar 'aib. Khiyar conditions, khiyar ta'yin, khiyar ru'yah and khiyar that have not been implemented are khiyar majlis.